Development of a Village Youth Entrepreneurship Model to Increase the Income of Wetland Village Communities - Anisah, Hastin Umi; Isnawati; Rifqi Novriyandana; Nor Hikmah (Open Access Indonesia Journal of Social Sciences, 2023)
The low competitiveness of human resources is highly correlated with the low potential and ability of the people's economy, which leads to higher poverty rates. Intervention in the economic capacity of the community needs to be carried out in order to prevent the negative effects of the lack of quality human resources. Entrepreneurship is a very important aspect to be developed in society as a form of economic intervention. This study aimed to develop a village youth entrepreneurship model to increase the income of wetland villages. This study is an observational study in Beranggas Timur Village, Alalak District, Barito Kuala Regency, South Kalimantan Province, Indonesia. Data analysis was carried out with PLS-SEM facilitated by SmartPLS 3. Creativity has no significant effect on entrepreneurial intention; Imagination has no significant effect on entrepreneurial intention; and personality has a significant effect on entrepreneurial intention.